Open innovation in the shared mobility market - Katarzyna Turoń; Andrzej Kubik (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The market for shared mobility services is growing very quickly. New types of vehicles have been introduced, and the offer of available services and functionalities has expanded, the purpose of which is to improve the quality of service. Despite all the improvements, it is still not possible to speak of achieving full availability of systems that meet the needs of users. This is due to the reluctant involvement of operators of shared mobility systems in joining Mobility as a Service platforms based on the idea of open innovation. The aim of the article is to analyze the factors influencing the limitations in the development of open innovations in the form of Mobility as a Service (MaaS) services. The authors focus on identifying the challenges and concerns faced by shared mobility service providers. The article supports the development of the concept of open innovation in shared mobility services. It also contains practical recommendations for the development of MaaS systems. The results of the developed research can be used by operators of shared mobility services, transport authorities, or IT service providers providing MaaS services to strengthen cooperation and integration using the language of mutual benefit.
Keywords: 650; MaaS; Mobility as a Service; open innovation management; open innovations in shared mobility; shared mobility; shared mobility development; sustainable transportation; urban transport systems